Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.15585/mmwr.mm6932e3
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization Rates and Characteristics of Children Aged <18 Years Hospitalized with Laboratory-Confirmed COVID-19 — COVID-NET, 14 States, March 1–July 25, 2020

Abstract: This report has been corrected. The definition of pediatric obesity was incorrectly stated in the text of the report and in the Table footnote; however, the analysis was correct and used the CDC definition of pediatric obesity for children aged ≥2 years (body mass index [kg/m2] ≥95th percentile for age and sex based on CDC growth charts).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

44
440
6
8

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 493 publications
(498 citation statements)
references
References 9 publications
(12 reference statements)
44
440
6
8
Order By: Relevance
“…The vast majority of pediatric SARS-CoV-2 infections are asymptomatic or cause only mild symptoms. In the United States, pediatric hospitalization rates are low (8.0/100,000 persons) compared with those for adults (164.5/100,000 persons) (11). Although one-third of hospitalized children require intensive care (similar to adults), severe COVID-19 and death rarely occur in children and are usually limited to those with underlying health conditions (including obesity) or infants (12).…”
Section: A Sars-cov-2-associated Hyperinflammatory Syndrome In Childrenmentioning
confidence: 99%
“…The vast majority of pediatric SARS-CoV-2 infections are asymptomatic or cause only mild symptoms. In the United States, pediatric hospitalization rates are low (8.0/100,000 persons) compared with those for adults (164.5/100,000 persons) (11). Although one-third of hospitalized children require intensive care (similar to adults), severe COVID-19 and death rarely occur in children and are usually limited to those with underlying health conditions (including obesity) or infants (12).…”
Section: A Sars-cov-2-associated Hyperinflammatory Syndrome In Childrenmentioning
confidence: 99%
“…As infections with SARS-CoV-2 and its associated illness, COVID-19, have surged across the world, multiple studies have identified higher rates of infection, hospitalization, and mortality among minority populations. [1][2][3][4][5][6][7][8][9][10][11][12] Disparities in infection rates exist even among healthcare workers 13 and children, 14,15 with disparities in mortality rates greatest among young individuals 16 and growing as the pandemic spreads. 17 To date, the relative contributions of pathophysiologic and socioeconomic factors contributing to these disparities remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…39 Data indicate that children made up only 0.5%-3.7% of all hospitalisations and between 0.2%-8% of paediatric cases were hospitalised. 40 Regarding those hospitalised, recent numbers suggest up to 33% of hospitalised children require care in an Intensive Care Unit (ICU), 40 a rate similar to adult ICU admissions. Investigation into the children who are requiring ICU-level care revealed that 83% had underlying medical conditions.…”
Section: Safer Infection For Healthy Childrenmentioning
confidence: 99%
“…While an estimated 2% ICU admission rate of known paediatric infections with SARS-CoV-2 may seem relatively insignificant, incidence of anaphylaxis after vaccine injection is less than 1/10 000 of the rate of ICU admission for children with SARS-CoV-2, for example. 40 In addition, our understanding of the COVID-related risks to children is still evolving. Beginning in May of 2020, there was an increasing number of cases of a disorder connected to SARS-CoV-2 infection, Multisystem Inflammatory Syndrome in Children (MIS-C).…”
Section: Safer Infection For Healthy Childrenmentioning
confidence: 99%
See 1 more Smart Citation